Point-of-care viral load testing among adolescents and young adults living with HIV in Haiti: a randomized control trial. Issue 4 (3rd April 2022) - Reif, Lindsey K.; Belizaire, Marie Elmase; Rouzier, Vanessa; Seo, Grace; Severe, Patrice; Bajo Joseph, Joseph-Marie; Joseph, Bernadette; Apollon, Sandra; Pape, Jean W.; McNairy, Margaret L.; Elul, Batya; Fitzgerald, Daniel W.; et al.
ABSTRACT: HIV viral load (VL) monitoring can reinforce antiretroviral therapy (ART) adherence. Standard VL testing requires high laboratory capacity and coordination between clinic and laboratory which can delay results. A randomized trial comparing point-of-care (POC) VL testing to standard VL testing among 150 adolescents and young adults, ages 10-24 years, living with HIV in Haiti determined if POC VL testing could return faster results and improve ART adherence and viral suppression. Participants received a POC VL test with same-day result (POC arm) or a standard VL test with result given 1 month later (SOC arm). POC arm participants were more likely to receive a test result within 6 weeks than SOC arm participants (94.7% vs. 80.1%; p1000 copies/ml and low self-reported ART adherence was stronger in the POC arm (OR: 6.57; 95%CI: 2.12-25.21) than the SOC arm (OR: 2.62; 95%CI: 0.97-7.44) suggesting more accurate self-report in the POC arm. POC VL testing was effectively implemented in this low-resource setting with faster results and is a pragmatic intervention that may enable clinicians to identify those with high VL to provide enhanced counseling or regimen changes sooner. Trial registration: ClinicalTrials.gov identifier: NCT03288246.